STATESMAN: PRETENSION TO ANALYSIS OF CONCEPT - Jokubaitis, Alvydas; Lopata, Raimundas (Politologija, 2015)
The term statesman has got a positive connotation in Western political vocabularies. The situation in Lithuania is different. Peculiarities of political process lead to devaluation of the term. During the interwar period in Lithuania the term statesman was more often used by right-wing politicians as a reference designating qualitative evaluation of politicians and other state agents. Statesman got broader meaning and was used more often by Lithuanian emigrants in the USA. The Renaissance of the term was influenced by Anglo-Saxon political and cultural environment, nostalgia of lost statehood and striving to maintain political identity. In Post-Communist Lithuania thanks to historians the term statesman became one of the instruments in political vocabulary. For some political parties this concept is a tool to achieve political power. There are three conceptions of the term statesman – idealistic, realist and administrative-bureaucratic. Proponents of idealistic conception think that statesman has to establish important political principles for future generations, he has to see further and deeper than other political agents, be virtuous, just and capable of defending the liberal state. Proponents of this view think that statesman has to be moral authority. Realist conception of statesman is based on different understanding of the relationship between morality and politics. Realists are not advocates of immoral politics, but they think that some circumstances of political life make it necessary to raise the requirements of the state higher than those of morality. Nicollò Machiavelli formulated the idea that state has got its own autonomous foundations of existence which are different from those of morality and religion. He formed the idea that when there is an exceptional situation, statesman has to look to the interests of state and not those of morality. Henry Taylor is the creator of administrative-bureaucratic conception of statesman. He is of the opinion that a man who has mastered the art of implementation of political functions can make a righteous claim to the title of statesman.